Maternal B vitamin supplementation from preconception through weaning suppresses intestinal tumorigenesis in Apc1638N mouse offspring. Issue 12 (9th June 2011) - Ciappio, Eric D; Liu, Zhenhua; Brooks, Ryan S; Mason, Joel B; Bronson, Roderick T; Crott, Jimmy W
Abstract : Objective: Variations in the intake of folate are capable of modulating colorectal tumorigenesis; however, the outcome appears to be dependent on timing. This study sought to determine the effect of altering folate (and related B vitamin) availability during in-utero development and the suckling period on intestinal tumorigenesis. Design: Female wildtype mice were fed diets either mildly deficient, replete or supplemented with vitamins B2, B6, B12 and folate for 4 weeks before mating to Apc 1638N males. Females remained on their diet throughout pregnancy and until weaning. After weaning, all Apc 1638N offspring were maintained on replete diets for 29 weeks. Results: At 8 months of age tumour incidence was markedly lower among offspring of supplemented mothers (21%) compared with those of replete (59%) and deficient (55%) mothers (p=0.03). Furthermore, tumours in pups born to deficient dams were most likely to be invasive (p=0.03). The expression of Apc, Sfrp1, Wif1 and Wnt5a —all of which are negative regulatory elements of the Wnt signalling cascade—in the normal small intestinal mucosa of pups decreased with decreasing maternal B vitamin intake, and for Sfrp1 this was inversely related to promoter methylation. β-Catenin protein was elevated in offspring of deficient dams. Conclusions: These changes indicate a de-repression of the Wnt pathway in pups of deficient dams and form a plausible mechanism by which maternal B vitamin intake modulates tumorigenesis in offspring. These data indicate that maternal B vitamin supplementation suppresses, while deficiency promotes, intestinal tumorigenesis in Apc 1638N offspring.